Current State of the Art in Cysticercosis and Neurocysticercosis - Morales-Montor, Jorge; Landa, Abraham; Ignacio Terrazas, Luis (IntechOpen, 2021)
This book provides updated information to scientists and clinicians on taeniosis/cysticercosis, a parasitic infection caused by eating undercooked beef or pork that is a serious health and veterinary problem in many developing countries. It discusses incidence, risk factors, diagnosis, immunology, symptoms, rare manifestations, and advances in treatment including vaccination and novel drug therapies.